2013
DOI: 10.1097/icu.0b013e32835c8aba
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma therapy and ocular surface disease

Abstract: BAK-free and preservative-free therapies are becoming available but are not always a feasible alternative. It is important to recognize different clinical manifestations of allergy and chronic inflammation and to discuss options for patients experiencing OSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(35 citation statements)
references
References 57 publications
1
27
0
2
Order By: Relevance
“…The study was a retrospective evaluation of routine visits performed using slit-lamp examination and, at discretion of the physician, dying with fluorescein to evaluate parameters related to dry eye (break-up time, epithelial staining, and clearance of fluorescein). Due to the use of low-tech methods, underestimation of conditions such as DED, particularly in asymptomatic cases, is extremely likely; moreover, the population of this study is not fully representative of the whole population, as in our clinic, patients with glaucoma or corneal pathologies (who have a very high prevalence of OSD [12, 15, 16]) are directly referred to tertiary services. Nevertheless, we found a prevalence of OSD of about 10%, which is confirmatory of the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The study was a retrospective evaluation of routine visits performed using slit-lamp examination and, at discretion of the physician, dying with fluorescein to evaluate parameters related to dry eye (break-up time, epithelial staining, and clearance of fluorescein). Due to the use of low-tech methods, underestimation of conditions such as DED, particularly in asymptomatic cases, is extremely likely; moreover, the population of this study is not fully representative of the whole population, as in our clinic, patients with glaucoma or corneal pathologies (who have a very high prevalence of OSD [12, 15, 16]) are directly referred to tertiary services. Nevertheless, we found a prevalence of OSD of about 10%, which is confirmatory of the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma and dry eye are prevalent conditions that often coexist in patients [1]. Glaucoma affects more than 60 million people worldwide and even mild disease has a significant impact on quality of life (QoL) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Preservatives in glaucoma drops have been cited as the main culprit – studies have found that these preservatives decrease tear film stability and cause toxicity to the ocular surface epithelium in vitro and in vivo in both clinical and animal studies 8,9. As such, some propose the use of preservative-free IOP-lowering eye drops.…”
Section: Discussionmentioning
confidence: 99%
“…Topical ocular IOP-lowering drugs are believed to trigger or exacerbate OSD by inducing ocular surface damage, especially if they contain preservatives, such as benzalkonium chloride (BAK) 12. Preservatives in eye drops have been shown to be toxic to the ocular surface epithelium and decrease tear film stability 8,9. Topical glaucoma medications have also been associated with alterations in Meibomian gland function and morphology,3 tear film instability,1013 decreased tear turnover and tear production,14–16 corneal anesthesia,17,18 corneal epithelial barrier dysfunction19,20 and inflammatory changes in the conjunctiva, ultimately resulting in OSD 2124…”
Section: Introductionmentioning
confidence: 99%